COMMUNITY SERVICES: OPTIMILIZATION INDIGENOUS COMMUNITY OF CIREUNDEU IN ADAPTING FOOD RESILIENCE TO SUPPORTING SDGs DESA AGENDA - Kunkurat; Tino Rila Sebayang; Apsha Luthvia Irza; Muhandis Rajab (Pasundan International of Community Services Journal (PICS-J), 2025)
The world has faced the threat of climate change, included Indonesia. Climate change has a negative impact on human life being, especially in the agricultural sector which provides basic human needs. Southeast Asia region including Indonesian, culturally make the rice as a staple main commodity of their lives. However, the difficulty with rice as a staple amidst climate change circumstances is required the high amount of water, while the earth’s temperature is getting hotter by the day, making it more likely that droughts will lead to crop failure. Therefore, food diversification is needed to replace the main commodities such as cassava and corn. Indigenous community of Cireundeu has diversified its food from rice to cassava as the main commodity. However, they have diversified, it does not mean the impact of climate change has stopped. This community services program in indigenous community of Cireundeu is expected to be able to provide solutions to these problems by according to Sustainable Development Goals Desa Agenda. Team of community services would be carried out using various methods, one of which involves participation from partners.